Communicative language teaching CLT activities to lower foreign language speaking anxiety in first bachillerato at unidad educativa fiscal Batalla de Tarqui during the school year 2016 - 2017 - Rosero Ruiz, Erika Sophia (2016)
The learning of a new Language is considered by many individuals as a hurdle task to achieve even more when the learning is just related to the ability of speaking the new language. Indeed, speaking a second language is a situation that triggers the possibility of experiencing a subjective feeling (anxiety) which when is linked with a foreign language is known as the foreign language speaking anxiety. Nevertheless, this issue is unknown by a significant number of educators. As a result, they attribute this phenomenon as a lack of interest to the learning of the foreign language rather than as an issue that learners can suffer especially when they have to accomplish communicative activities. That is why; it was proposed the application of activities (CLT activities) that can cope with the foreign language speaking anxiety. Thus, the objective of this study was to determine if these kinds of activities could reduce the level of speaking anxiety in them……